Pentingnya Motivasi Belajar Dalam Meningkatkan Hasil Belajar Siswa - Yogi Fernando; Popi Andriani; Hidayani Syam (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Learning motivation is one of the factors that determine the learning outcomes of students, a person will get the desired results in learning if there is a desire to learn in him. Motivation acts as a driver for the achievement of good results. A person will be encouraged to do an activity because there is motivation in him. The existence of high motivation in learning will achieve optimal results. The purpose of the research to be achieved is to determine the relationship between learning motivation and student learning outcomes, The research method in this study is a literature review (Library Research), namely in literature research. Based on the results of research that the learning motivation possessed by students in every learning activity plays a role in improving student learning outcomes, students who have high motivation in learning will likely obtain high learning outcomes as well.